The role of Green Building Information Modeling (GBIM) in promoting architectural sustainability - Yousif Al-Mashhadani Mays; Abdulmunem Al-Tameemi Osamah (E3S Web of Conferences)
Green Building Information Modeling (Green BIM) is a critical instrument for promoting sustainable architecture, given that it integrates environmental sustainability principles into building design and construction. By utilizing highly advanced digital technology, Green BIM optimizes energy efficiency, reduces environmental impact, and enhances resource allocation throughout a building’s lifecycle. This paper analyzes Green BIM’s role in promoting sustainability in new buildings as well as existing buildings. The study begins with emphasizing the importance of Green BIM in reducing the carbon footprint of the built environment. A comprehensive review of the literature and previous research is conducted to examine the benefits, challenges, levels of development, data requirements, and functionalities of Green BIM. The study then discusses selected international and regional case studies, in addition to a specific case study in Iraq, to assess the application and effectiveness of Green BIM in achieving sustainability. Finally, a theoretical Analysis of Green BIM’s Environmental Impact study is presented, criticizing the environmental benefits and implications of incorporating Green BIM into design and construction practices.